Identifying “free” and “bound” lipid fractions in stalagmite samples: An example from Heshang Cave, Southern China - Huang, X.; Jingwei, C.; Pu, Y.; Huang, J.; Blyth, Alison (Pergamon, 2008)
Stalagmites are good archives for paleoecological change, as they are easy to date, and contain multiple environmental proxy records, including climatic records from oxygen isotopes. Lipid biomarkers preserved within stalagmites have recently been used to investigate changes in the overlying soil and vegetation. However, the understanding of lipid records from stalagmites is still at an early stage, and is hindered by the low abundances of lipids preserved and the complexity of the organic matter signal. Here the first results of a sequential extraction procedure are presented, that enables examination of the distribution patterns of “free” (solvent extraction) and “bound” (including physically bound within the calcite matrix and chemically bound to macromolecules) lipids in a stalagmite from southern China. In both groups the dominant compounds are saturated fatty acids, which are an order of magnitude more abundant in the “bound” phase. n-alkanes and n-alcohols chiefly appear in the “free” lipids. In contrast, 3-hydroxy acids are predominantly released under strong acid reflux conditions, suggesting a principal input from bacterial membrane compounds. A direct comparison between the present results and the published data from an Ethiopian stalagmite shows significant differences in the lipid signals from separate sites, with a stronger microbial signal in the Chinese sample. This preliminary investigation of lipid distributions in different modes highlights the importance of microbial geochemical processes in karst systems and supports the use of stalagmites in paleoecological reconstruction.